2004
DOI: 10.1007/s00405-004-0824-y
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal partial laryngectomy for supraglottic squamous cell carcinoma

Abstract: Between 1981-1999, 75 patients treated for supraglottic SCC with horizontal supraglottic laryngectomy (HSL) at the Otolaryngology Head and Neck Surgery Department of Lausanne University Hospital were retrospectively studied. There were 16 patients with T1, 46 with T2 and 13 with T3 tumors. Among these, 16 patients (21%) had clinical neck disease corresponding to stage I, II, III and IV in 12, 39, 18 and 6 patients, respectively. All patients had HSL. Most patients had either elective or therapeutic bilateral l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…The local control rate was 90.3% and the 5-year overall survival rate 52%. Similar results were published by Bron et al [163] for 75 patients with T1-T3 supraglottic carcinomas. In this series, the 5-year local control rate was 92.5%, the organ preservation rate was 98.5%, and the 5-year overall survival rate was 75%.…”
Section: Supraglottic Carcinomassupporting
confidence: 91%
“…The local control rate was 90.3% and the 5-year overall survival rate 52%. Similar results were published by Bron et al [163] for 75 patients with T1-T3 supraglottic carcinomas. In this series, the 5-year local control rate was 92.5%, the organ preservation rate was 98.5%, and the 5-year overall survival rate was 75%.…”
Section: Supraglottic Carcinomassupporting
confidence: 91%
“…In other studies including ours, although the presence of nodal metastasis did reveal worse prognosis and low DFS, it did not reach significant levels. [14] Suoglu et al [8] and Joo et al, [3] both mentioned that in patients with PES invasion there were higher incidences of cervical nodal metastasis compared to patients with no invasion. We know that laryngeal cancers arising from the supraglottic larynx metastasize to lymphatics via the PES draining through the thyrohyoid membrane.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] There are few well-known factors that influence survival rates in patients who underwent open SGL such as pathological stage, pathological nodal status, cartilage invasion, extralaryngeal invasion and PES invasion. [5,6,[13][14][15][16] Among these negative prognostic factors, cervical lymph node metastasis was stated to cause worse prognosis by upgrading the disease to an advanced stage. Joo et al [3] showed a significant correlation between cervical nodal metastasis and DFS in patients who underwent supracricoid laryngectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The respiration function was interpreted based on the decannulation time. Different authors, including Ulusan et al (11) and Bron et al, [12] have reported a mean decannulation time of 17 days for patients who undergo SGHL. This time for patients in the present study was consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%